Tugas Dan Tanggung Jawab Orangtua Dalam Mendidik Iman Anak Pada Masa Kini - Evimawati Harefa (Jurnal Magistra, 2024)
Parents as the main educators of their children's faith means that parents must actively educate their children and be involved in their children's faith education process. Parents themselves must practice their faith, strive to live holy lives, and continue to apply the teachings of the faith in family life at home. Educating children in matters of faith is actually not difficult, because it can start from simple things. However, it requires commitment and sacrifice on the part of the parents, for example: praying with the children and reading the Holy Bible to them, bringing the children to the Holy Mass and afterward explaining to the children its meaning, giving warnings if the children make mistakes using the language of love.